Pengaruh Pemotongan Bagian Tubuh yang Berbeda terhadap Waktu Moulting dan Ukuran Kepiting Bakau (Scylla serata) - Adi Wibowo; Juliana; Sutianto Pratama Suherman (Transbahasa, 2025)
This study aims to determine the effect of different body part amputations on the moulting time and size of mangrove crabs (Scylla sp.) and to identify the most effective amputation method for accelerating moulting and enhancing growth. The research was conducted in Kantanan Village, Bokat District, Buol Regency, Central Sulawesi Province. A Completely Randomized Design (CRD) was applied with four treatments and five replications, totaling 20 experimental units. The collected data were analyzed using ANOVA to assess the significance of treatment effects. Data collection involved direct observation in aquaculture ponds and literature studies to support findings with relevant references. The observation technique was used to monitor the moulting process and crab growth based on research indicators. Meanwhile, the literature study involved reviewing books and journals related to the biology and cultivation of mangrove crabs. The results indicate that body part amputation influences moulting time and crab size. The treatment involving locomotor limb amputation resulted in the best growth performance compared to other treatments. This study recommends stricter water quality control in future research to ensure an optimal environment for mangrove crab growth and moulting.